Accountability through participation : developing workable partnership models in the health sector. - Cornwall, Andrea (2000)
Presents some of the principal themes emerging from articles included in this issue and workshop discussions. Focuses on building effective participation as well as some of the many issues that arise in moving towards more active citizen engagement with service provision.